Methane flux from high-yielding Inpari rice varieties in Central Java, Indonesia - Anicetus Wihardjaka; Eni Yulianingsih; Hesti Yulianingrum (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2020)
Rice cultivation is a source of greenhouse gas emissions, particularly methane (CH4). One of the factors that affect CH4 emissions from rice fields is rice cultivar. In this study, a field experiment was conducted to determine CH4 emissions from various high-yielding inbred varieties and the relationship between CH4 emissions and rice growth parameters. The field experiment was conducted in Jaken, Pati Regency, Central Java province, during the wet season of 2014/2015. The experiment was arranged using a randomized block design with three replications and several cultivar treatments (Inpari 13, 18, 19, 20, 23, 24, 29, 30, 31, 32, and 33, with Ciherang as the comparison cultivar). The data collected includes CH4 flux, plant height, tiller number, biomass, grain yield, and root aerenchyma area. The CH4 flux was measured at several critical growth stages. The Inpari 24, Inpari 13, and Inpari 19 demonstrated CH4 emissions reduced by as much as 36.1%, 32.8%, and 21.3%, respectively, compared to Ciherang. The Inpari 13 and Inpari 24 varieties had significantly lower emission indices than Ciherang and the other Inpari varieties, with 17 and 20 g CH4 per 1 kg grain yield, respectively. CH4 flux was found to correlate significantly with tiller number per hill, total biomass, and root aerenchyma area at the panicle initiation growth stage.